Using Peer-Learning and Game-Based Instruction for Achieving Long-Lasting Knowledge of Cybersecurity in Primary Schools - Maja Videnovik; Vladimir Trajkovik; Tone Vold; Linda Vibeke Kionig; Ana Madevska Bogdanova; Sonja Filiposka (IEEE Access)
As the world becomes increasingly dependent on technology, cybersecurity education has become more important than ever before. However, teaching cybersecurity to primary school students faces several challenges, including limited resources, lack of specialized teachers, and age-appropriate content. In this paper, we propose a new and innovative approach for teaching cybersecurity to primary school students, which addresses these challenges. The proposed approach, implemented with 339 students in five primary schools in North Macedonia, combines peer learning and a game-based approach to develop students’ communication, collaboration, and critical thinking skills, and create engaging learning environments. Upper-grade students deliver lectures and create educational games for their lower-grade peers, fostering learning communities where students share their knowledge and experiences, and learn from one another’s diverse perspectives. The game-based approach is used to create interactive and engaging learning environments where students design or play games to develop their critical thinking skills and empower their cybersecurity knowledge. Initial evaluation results after one year of implementing this cybersecurity learning concept, carried out with 124 students from three participating schools, indicate that students exposed to peer learning and a game-based approach could retain their knowledge, with their knowledge levels outperforming those of students who received traditional classroom instruction. Moreover, students have positive attitudes toward implemented approach and believe that it has effectively enhanced their communication, collaboration, and critical thinking skills while creating exciting and engaging learning environments. These findings suggest that this new and innovative approach has the potential to effectively teach cybersecurity to primary school students, fostering long-lasting knowledge and creating engaging learning environments. Its implementation can be easily adopted in different educational contents and surroundings.